Why do Children Hit Others? Kindergarten Teachers’ Beliefs about Aggressive Behavior in Children (Revista Peruana de Investigación Educativa, 2010)
This study was aimed at exploring teachers’ beliefs about children’s aggressive behavior. Through in depth interviews, teachers’ beliefs in four different areas were explored: a) their conception of aggressiveness, b) their ideas about its causes, c) the effects that aggressive behaviors have in the classroom dynamics, and d) their beliefs about how these conducts should be managed in the classroom. Participants were 10 teachers and 8 teachers’ assistants, who made up the total teachers team of a public early childhood education school in the city of Lima. Results show that participants have difficulties defining the concept of aggression. They also believe that these problematic behaviors stem mainly from home, and so, parents are viewed as the only responsible for the problems and the ones who must find solutions, by themselves. The study ends up by recommending building school opportunities for teachers to exchange ideas and reflect upon their own practice and their responsibility in the education of children in pre-school age.
Keywords: preschool teachers; aggressiveness; student behavior; early childhood education